2010
DOI: 10.1002/jcp.22347
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin promotes actin stress fiber formation in RPE through Rho/ROCK‐mediated MLC phosphorylation

Abstract: The retinal pigment epithelium (RPE) forms the outer blood-retina barrier (BRB). Most retinal diseases involve BRB breakdown, whereupon thrombin contained in serum directly contacts the RPE. Thrombin is known to promote actin stress fiber formation, an important determinant in eye diseases involving the epithelial-mesenchymal transition (EMT) and migration of RPE cells, such as proliferative vitreoretinopathy. We analyzed thrombin effect on signaling pathways leading to myosin light chain (MLC) phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 51 publications
2
34
0
Order By: Relevance
“…Inhibition of ROCK1 expression blocks LIMK2/cofilin phosphorylation and subsequent stress fiber formation (38,39). MLC stimulates the formation and stabilization of actin stress fibers (40). In this study, we found that HIF-3a transcriptionally regulates RhoC and ROCK1 and enhances phospho-cofilin, and phospho-MLC2 levels, demonstrating activation of RhoC-ROCK1 signaling.…”
Section: Discussionsupporting
confidence: 53%
“…Inhibition of ROCK1 expression blocks LIMK2/cofilin phosphorylation and subsequent stress fiber formation (38,39). MLC stimulates the formation and stabilization of actin stress fibers (40). In this study, we found that HIF-3a transcriptionally regulates RhoC and ROCK1 and enhances phospho-cofilin, and phospho-MLC2 levels, demonstrating activation of RhoC-ROCK1 signaling.…”
Section: Discussionsupporting
confidence: 53%
“…It was found that RPE cells lost their initial phenotype, dedifferentiated and acquired mesenchymal migratory morphology and cytoskeleton proteins (Casaroli-Marano et al, 1999). Recently thrombin (see above) pretends to play a promoting role in actin stress fiber formation, an important determinant in eye diseases involving transformation and migration of RPE cells (Ruiz-Loredo et al, 2011 Earlier we showed a decrease of fibronectin in Bruch membrane and its redistribution in RPE after NR detachment in the newt (Grigoryan et al, 1990). Similar results were obtained by Ortiz and co-authors (1992): at the beginning of RPE cell transdifferentiation in the eye of the adult newt, fibronectin was the first to appea r i n t h e c e l l b o r d e r o f t h e n e w f o r m i n g neuroepithelium.…”
Section: Remodeling Of Extracellular Matrix (Ecm) and Rpe Cytoskeletonmentioning
confidence: 98%
“…Collectively, these observations suggest a model in which Rho and ROCK serve as important mediators downstream of GPER and are required for GPER to activate TAZ. The Rho/ROCK pathway potently modulates cellular actin dynamics, particularly stress fiber formation, in response to various GPCR agonists such as LPA or thrombin (42,43). We therefore examined whether cytoskeletal reorganization contributes to TAZ activation in response to G1 stimulation.…”
Section: Gper Expression Is Elevated In Idc Of the Breastmentioning
confidence: 99%